DEVELOPING MEDIA IN TEACHING WRITING DESCRIPTIVE TEXT BY USING PREZI FOR GRADE VII OF SMP MUHAMMADIYAH 1 MEDAN - Erlita Gusra; Nora Ronita Dewi; Yeni Elita (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2019)
The aim of this study was to develop media in Teaching Writing Descriptive Text for grade VII of SMP Muhammadiyah 1 Medan students. This study was conducted by using Research and Development (R & D) design through six stages; gathering data and information, analyzing data, designing media, validating by the experts, revising and final products. The subject of the study was grade VII of SMP Muhammadiyah 1 Medan. The data were gathered by administering interview to English teacher and distributing questionnaire to 35 respondents to get the students’ needs. The interview and questionnaire result prove that the students need English media in teaching writing which can motivate the students to understand about the descriptive text. The product has been validated by an English lecturer and an English teacher with the percentage was 93,6%. The product was categorized as “Excellent” media in teaching writing descriptive text. The result of the products was presentation that contain in audio-visual media to be used in mastering the descriptive text writing. Keywords : Prezi, Descriptive Text, Research and Development (R & D).